Mechanisms of Action and Current Research Status of New Drugs For Cardiovascular Diseases (Cvds) - Wang, Shaoyang (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Cardiovascular diseases (CVDs) remain one of the leading causes of death and disability worldwide, posing a significant threat to global public health. In recent years, with the advancements in molecular biology and genomics, the development of new drugs for CVDs treatment has made substantial progress, particularly in the fields of anti-inflammatory, anti-fibrosis, and angiogenesis therapies. This thesis investigates the mechanisms of action of these innovative drugs and their clinical applications. Firstly, the critical role of anti-inflammatory drugs in CVDs is analyzed, highlighting how novel anti-inflammatory agents, such as IL-6 inhibitors, modulate immune responses to reduce cardiovascular inflammation. Secondly, anti-fibrotic drugs, such as TGF-β inhibitors, are discussed in detail, focusing on their ability to inhibit fibrosis progression and improve cardiac function by reversing myocardial fibrosis. Additionally, angiogenesis-based drugs, which promote endothelial cell repair and regeneration, are explored for their potential in enhancing microcirculation in the cardiovascular system. The thesis also delves into the prospects of personalized medicine and gene therapy in the development of new CVDs treatments. Emerging technologies, such as multi-target combination therapies, gene editing, and nanomedicine carriers, are expected to bring breakthroughs in the treatment of CVDs. This paper summarizes current research progress and explores future directions, providing theoretical foundations and practical insights for the development of novel drugs for CVDs.